Phonon scattering and heat transfer by “diffusive” modes in solid C₆H₆ - Pursky, O.I.; Konstantinov, V.A. (Condensed Matter Physics, 2006)
The isochoric thermal conductivity of solid C₆H₆ is described within a model in which the heat is transferred by phonons and above the phonon mobility edge by “diffusive” modes migrating randomly from site to site. The mobility edge ω₀ is found from the condition, that the phonon mean-free path restricted by the examined mechanisms of scattering cannot become smaller than half the wavelength. The contributions of phononphonon, one and two-phonon scattering to the total thermal resistance of solid C₆H₆ are calculated under the assumption of additive contribution of different scattering mechanisms. Significant deviations from the dependence Λ ∝1/T are explained by thermal conductivity approaching its lower limit.